Contribution to the knowledge of Crataego-Prunetea Tüxen 1962 class in Bulgaria - Vassilev, Kiril; Velev, Nikolay; Nazarov, Momchil (Hacquetia, 2020)
Mantle vegetation includes plant communities dominated mostly by shrubs and occurs in habitats where the typical tree layers meet difficulties to evolve. This study was conducted in three areas of Bulgaria – Western Balkan Range, Western Sredna Gora Mt. and the Fore-Balkan. Numerical classification and ordination were performed by PC-ORD and JUICE software packages. Diagnostic species were determined by calculating the Phi-coefficient. Two associations and one plant community of the Berberidion alliance were recognized – Corno-Ligustretum Horvat ex Trinajstić & Z. Pavletić 1991, Pruno spinosae-Ligustretum vulgaris Tüxen 1952 and Elytrigia repens-Crataegus monogyna community. The latter considered as a successional stage of shrub encroachment into the grasslands. Its species composition is very close to that of the ass. Corno-Ligustretum. The species composition of ass. Pruno-Ligustretum represents a mixture of species characteristic for dry and mesic grasslands, fringe and forest vegetation. The Crataego-Prunetea class is still poorly studied in Bulgaria and much more data from all regions in the country have to be collected.